Representations of detention and other pains of law enforcement in police museums in Ontario, Canada. (24th March 2019) - Ferguson, Matthew; Piché, Justin; Walby, Kevin
ABSTRACT: Police museums have been described as dark tourism destinations that depict death and suffering, yet rarely have they been conceptualised as a form of penal tourism. Applying Diarmaid Harkin's notion of 'pains of policing' to police museums in Ontario, Canada we illustrate how these sites engage in punishment memorialisation. Police museums, which are increasingly staged in the front of police headquarters, are one of the ways policing organisations communicate with the public about their practices, past and present. Engaging with literature on public meanings of police memorialisation, we show how use of force, arrest, interrogation, detention, and other aspects of law enforcement and penality are represented in these museum settings. Drawing from field notes and visual analysis, we argue that these depictions deflect culpability and blame for police violence and abuses, which are normalised in these representations. In conclusion, we reflect on what our findings mean for literature on police museums specifically, and dark and penal tourism sites more broadly.